Anisotropic conductive adhesive, preparation method and electronic component

By using the nuclear -shell structure conductive particles in various heterosexual conductivity, the problem of vertical electrical interconnection is difficult to achieve vertical electrical interconnection under low pressure, and the reliable vertical electrical interconnection and insulation effect under low pressure are achieved.

CN119371922AActive Publication Date: 2025-01-28SHENZHEN INST OF ADVANCED ELECTRONICS MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411662983.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Traditional anisotropic conductive adhesives are difficult to achieve stable and reliable vertical electrical interconnection at low pressures, especially in scenarios with small-sized chips and flexible substrates.

Method used

The nuclear conductive particles are adopted. The nucleus layer of the conductive particles includes liquid metal. The shell layer includes a metal layer of 50nm to 500nm thick, combined with epoxy resin and curing agent to prepare a new type of heterosexual conductivity.

Benefits of technology

The electrical glue can achieve vertical conductivity and horizontal insulation under the pressure of 1N to 3N, improve the performance of reliable vertical electrical interconnection under low pressure, and avoid the problem of the cracking of the conductive particle shell layer and the outflow of liquid metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005145776230000131
    Figure BDA0005145776230000131
  • Figure BDA0005145776230000141
    Figure BDA0005145776230000141
  • Figure HDA0005145776280000011
    Figure HDA0005145776280000011
Patent Text Reader

Abstract

The invention discloses an anisotropic conductive adhesive, a preparation method and an electronic element, and relates to the technical field of packaging. The anisotropic conductive adhesive provided by the embodiment of the invention comprises the following components in parts by mass: 50-100 parts of epoxy resin; 0.5 to 30 parts of a curing agent; the conductive particles are of core-shell structures, core layers of the conductive particles comprise liquid metal, and shell layers of the conductive particles comprise metal layers. According to the anisotropic conductive adhesive, the conductive particles with the core-shell structures are added into the anisotropic conductive adhesive, so that the conductive particles have relatively good plasticity or deformability, and the reliable vertical electrical interconnection of the anisotropic conductive adhesive in a low-pressure bonding scene can be improved; and the problem that when the conductive adhesive in the embodiment of the invention is pressed, the shell layers of the conductive particles in the conductive adhesive are broken, so that the liquid metal in the conductive particles flows out, and the anisotropic conductive adhesive fails is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of packaging technology, and in particular to an anisotropic conductive adhesive and a preparation method thereof, and an electronic component. Background Art

[0002] Anisotropic conductive paste (ACP) is a special conductive functional material that can conduct electricity along the pressure direction and insulate in the direction perpendicular to the pressure after hot pressing and curing. At the same time, ACP has shown great application potential in the field of high-density, narrow-pitch electrode vertical electrical interconnection due to its advantages such as high efficiency and low cost. Conductive particles are evenly dispersed in the insulating organic material. When vertical pressure is applied, the chip electrodes and substrate pads capture some of the conductive particles, which can achieve vertical conductivity and horizontal insulation. It is used in ultra-narrow pitch packaging such as flexible electronic devices and liquid crystal displays, such as radio frequency identification (RFID) electronic tag packaging.

[0003] The main components of anisotropic conductive adhesive are polymer resin matrix and conductive particles. The polymer resin serves as the matrix and plays a role of mechanical support after curing. The conductive particles have good electrical properties and form a conductive path by contacting the upper and lower interfaces. Factors that affect the curing performance of anisotropic conductive adhesive include the type of curing agent, the amount of curing agent added, the curing temperature and the curing time. By adjusting the above parameters, the rapid curing of anisotropic conductive adhesive can be achieved to meet the needs of efficient and rapid packaging of RFID electronic tags.

[0004] However, the conductive particles used in traditional anisotropic conductive adhesives, such as silver (Ag), nickel (Ni) and gold (Au), often require higher bonding pressures to achieve stable and reliable electrical interconnection. They are not suitable for certain scenarios such as small-size chips and flexible substrates that require vertical electrical interconnection under low pressure.

[0005] Therefore, developing a new type of anisotropic conductive adhesive to meet the requirements of reliable vertical electrical interconnection in low-voltage bonding scenarios is of great significance in the electronic packaging industry. Summary of the invention

[0006] In view of this, the present application provides an anisotropic conductive adhesive and a preparation method, and an electronic component, aiming to improve the problem that the existing anisotropic conductive adhesive does not meet the vertical electrical interconnection requirements in low-voltage bonding scenarios.

[0007] In a first aspect, an embodiment of the present application provides an anisotropic conductive adhesive, which comprises, by weight: 50 to 100 parts of epoxy resin;

[0008] 0.5 to 30 parts of curing agent; and

[0009] 10 to 40 parts of conductive particles with a core-shell structure, wherein the core layer of the conductive particles comprises liquid metal, and the shell layer of the conductive particles comprises a metal layer.

[0010] In some embodiments of the present application, the thickness of the metal layer is 50nm to 500nm.

[0011] In some embodiments of the present application, the thickness of the metal layer is 60nm to 200nm; and / or

[0012] The particle size of the conductive particles is 1 μm to 5 μm; and / or

[0013] The anisotropic conductive adhesive further comprises at least one of a diluent, a thixotropic agent, and an inorganic filler; and / or

[0014] The conductive particles of the core-shell structure are 25 to 40 parts.

[0015] In some embodiments of the present application, the liquid metal includes one or more of gallium, bismuth, cadmium, tin, lead, and indium; and / or

[0016] The material of the metal layer includes at least one of silver, copper, aluminum, gold, nickel and zinc.

[0017] In some embodiments of the present application, the liquid metal includes one or more of gallium, bismuth, cadmium, tin, lead, indium, bismuth-gallium alloy, gallium-indium alloy, gallium-indium-tin alloy, and indium-tin alloy; and / or

[0018] The material of the metal layer includes silver, copper, aluminum and gold.

[0019] In some embodiments of the present application, the liquid metal is a gallium-indium alloy, and the material of the metal layer is silver.

[0020] In some embodiments of the present application, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, and alicyclic epoxy resin; and / or

[0021] The curing agent is one or more of dicyandiamide, aromatic diamines, imidazoles and hydrazides.

[0022] In some embodiments of the present application, the curing agent is composed of imidazoles and dicyandiamides, and the mass ratio of the imidazoles to the dicyandiamides is (5-15): (5-15).

[0023] In some embodiments of the present application, the active diluent is 1 to 50 parts by weight; and / or

[0024] The diluent comprises a reactive diluent, and the reactive diluent is selected from one or more of propenyl glycidyl ether, phenyl glycidyl ether, ethylene glycol bisglycidyl ether with diepoxy groups, and resorcinol bisglycidyl ether; and / or

[0025] The thixotropic agent is 0.5 to 15 parts by mass; and / or

[0026] The thixotropic agent is selected from one or more of fumed silica, precipitated silica, organic bentonite, asbestos, kaolin, attapulgite, and emulsion-processed vinyl chloride compounds.

[0027] In some embodiments of the present application, under a bonding pressure of 1N to 3N, the anisotropic conductive adhesive is electrically conductive in the direction of the bonding pressure and is electrically insulated in a direction perpendicular to the bonding pressure.

[0028] A second aspect of the present application provides a method for preparing an anisotropic conductive adhesive, the preparation method comprising the following steps:

[0029] Weigh the conductive particles of the core-shell structure, epoxy resin and curing agent according to a preset ratio;

[0030] The conductive particles with the core-shell structure, epoxy resin and curing agent are mixed by using a mixing device to obtain anisotropic conductive adhesive;

[0031] The core layer of the conductive particles includes liquid metal, the shell layer of the conductive particles includes a metal layer, and the thickness of the metal layer is 50 nm to 500 nm.

[0032] In some embodiments of the present application, the step of preparing the conductive particles with a core-shell structure comprises:

[0033] obtaining a liquid metal microsphere suspension and a silver ammonia solution;

[0034] Adding the liquid metal microsphere suspension into the silver ammonia solution, stirring the reaction to obtain a dark brown conductive particle dispersion;

[0035] Conductive particles with a core-shell structure are obtained by filtering and drying, wherein the core layer of the conductive particles comprises liquid metal, and the shell layer of the conductive particles comprises a silver layer.

[0036] A third aspect of the present application provides an electronic component, comprising a first electrical connection portion, a second electrical connection portion and the anisotropic conductive adhesive, wherein the anisotropic conductive adhesive is used to electrically connect the first electrical connection portion and the second electrical connection portion in the direction of bonding pressure.

[0037] Beneficial effects:

[0038] In the present application, conductive particles with a core-shell structure are added to the anisotropic conductive adhesive so that the conductive particles have better plasticity or deformability, which is beneficial to improving the reliable vertical electrical interconnection of the anisotropic conductive adhesive in the present application in a low-pressure bonding scenario, and is beneficial to avoiding the problem that when the conductive adhesive in the embodiment of the present application is subjected to pressure, the shell layer of the conductive particles inside it breaks, causing the liquid metal in the conductive particles to flow out, thereby causing the anisotropic conductive adhesive to fail. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 The scanning electron microscope image and particle size dispersion image of the liquid metal microsphere suspension prepared in Example 1.

[0041] Figure 2 The scanning electron microscope image and particle size dispersion diagram of the LM@Ag conductive microspheres prepared in Example 1.

[0042] Figure 3 Cross-sectional scanning electron microscope image and element distribution diagram of the LM@Ag conductive microspheres prepared in Example 1.

[0043] Figure 4 FIG. 4 is a process diagram of bonding an RFID chip with anisotropic conductive adhesive in an embodiment of the present invention.

[0044] Figure 5 This is a SEM image of the cross-section of an RFID chip bonded with anisotropic conductive adhesive in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0047] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0048] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0049] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0050] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0051] Anisotropic conductive paste (ACP) is a special conductive functional material that can conduct electricity along the pressure direction and insulate in the direction perpendicular to the pressure after hot pressing and curing. At the same time, ACP has shown great application potential in the field of high-density, narrow-pitch electrode vertical electrical interconnection due to its advantages such as high efficiency and low cost. Conductive particles are evenly dispersed in the insulating organic material. When vertical pressure is applied, the chip electrodes and substrate pads capture some of the conductive particles, which can achieve vertical conductivity and horizontal insulation. It is used in ultra-narrow pitch packaging such as flexible electronic devices and liquid crystal displays, such as radio frequency identification (RFID) electronic tag packaging.

[0052] The main components of anisotropic conductive adhesive are polymer resin matrix and conductive particles. The polymer resin serves as the matrix and plays a role of mechanical support after curing. The conductive particles have good electrical properties and form a conductive path by contacting the upper and lower interfaces. Factors that affect the curing performance of anisotropic conductive adhesive include the type of curing agent, the amount of curing agent added, the curing temperature and the curing time. By adjusting the above parameters, the rapid curing of anisotropic conductive adhesive can be achieved to meet the needs of efficient and rapid packaging of RFID electronic tags.

[0053] However, the conductive particles used in traditional anisotropic conductive adhesives, such as silver (Ag), nickel (Ni) and gold (Au), often require higher bonding pressure to achieve stable and reliable electrical interconnection. They are not suitable for certain scenarios such as small-size chips and flexible substrates that require vertical electrical interconnection under low pressure.

[0054] Therefore, in the electronic packaging industry, it is of great significance to develop a new type of anisotropic conductive adhesive to meet the requirements of reliable vertical electrical interconnection in low-voltage bonding scenarios.

[0055] In view of this, an embodiment of the present application provides an anisotropic conductive adhesive, which comprises, by weight:

[0056] 50 to 100 parts of epoxy resin;

[0057] 0.5 to 30 parts of curing agent; and

[0058] 10 to 40 parts of conductive particles with a core-shell structure, wherein the core layer of the conductive particles comprises liquid metal, and the shell layer of the conductive particles comprises a metal layer.

[0059] Exemplarily, the mass fraction of the epoxy resin in the anisotropic conductive adhesive is 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and a value between any two of the above values.

[0060] Exemplarily, the mass fraction of the curing agent in the anisotropic conductive adhesive is 0.5 parts, 1 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, and a value between any two of the above values.

[0061] Exemplarily, the mass fraction of the conductive particles in the anisotropic conductive adhesive is 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, and values ​​between any two of the above values. Exemplarily, the thickness of the metal layer is 50nm, 60nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, and values ​​between any two of the above values.

[0062] In the present application, conductive particles with a core-shell structure are added to the anisotropic conductive adhesive, and the mass fraction of the conductive particles is 10 to 30 parts, so that the conductive particles can have better plasticity or deformability, which is beneficial to improving the reliable vertical electrical interconnection of the anisotropic conductive adhesive in the present application in a low-pressure bonding scenario, and is beneficial to avoiding the problem that when the conductive adhesive in the embodiment of the present application is subjected to pressure, the shell layer of the conductive particles inside it breaks, causing the liquid metal in the conductive particles to flow out, thereby causing the anisotropic conductive adhesive to fail.

[0063] It should be noted that the anisotropic conductive adhesive in the present application is different from the traditional conductive adhesive. The anisotropic conductive adhesive has a higher conductivity in the pressure direction (such as the vertical direction), and exhibits an insulating property in the non-pressure direction (such as the horizontal direction). This property enables the anisotropic conductive adhesive to effectively prevent short circuits when connecting electronic components (such as chips and circuit boards) while ensuring good electrical connections.

[0064] The anisotropic conductive adhesive in the embodiment of the present application can be used for packaging electronic components and electrodes in flip chips, radio frequency identification, and display panels. Exemplarily, the anisotropic conductive adhesive is used to electrically connect the first electrical connection part and the second electrical connection part in the electronic component in the direction of the bonding pressure.

[0065] It should be noted that the first electrical connection part and the second electrical connection part can be two electrical connection parts on the same electronic component, or two electrical connection parts on different electronic components, which is not limited here. Exemplarily, the first electrical connection part is an external pin on a chip, and the second connection part is an electrode sheet. The above-mentioned anisotropic conductive glue is applied to the first electrical connection part and / or the second connection part, and then the temperature and vertical pressure are applied by a hot press head to cure the anisotropic conductive glue on the first electrical connection part and the second connection part, thereby achieving electrical connection and packaging of the first electrical connection part and the second connection part.

[0066] In some embodiments of the present application, the thickness of the metal layer is 50nm to 500nm. Further, the thickness of the metal layer is 60nm to 200nm. Further, the thickness of the metal layer is 80nm to 120nm. In this way, it is beneficial to increase the plasticity of the conductive particles and to further improve the bonding performance of the conductive adhesive in the present application under low pressure. In some embodiments of the present application, the particle size of the conductive particles is 1μm to 5μm. Exemplarily, the particle size of the conductive particles (ie, D50) is 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm and values ​​between any two of the above values.

[0067] In some embodiments of the present application, the liquid metal includes one or more of gallium, bismuth, cadmium, tin, lead, and indium. Further, the liquid metal includes at least one of gallium (Ga) and a liquid metal alloy.

[0068] Specifically, the liquid metal alloy includes at least one of a bismuth-gallium alloy, a gallium-indium alloy, a gallium-indium-tin alloy, and an indium-tin alloy.

[0069] In some embodiments of the present application, the material of the metal layer includes at least one of silver (Ag), copper (Cu), aluminum (Al), gold (Au), nickel (Ni), and zinc (Zn). Further, the material of the metal layer includes silver (Ag), copper (Cu), aluminum (Al), and gold (Au).

[0070] In some embodiments of the present application, the liquid metal is a gallium-indium alloy, and the material of the metal layer includes silver (Ag), and the silver encapsulates the gallium-indium alloy therein. The shell density of the conductive particles in the structure of this embodiment is higher, and the deformability is higher, and the use of anisotropic conductive adhesive is conducive to further improving the stability of its vertical electrical interconnection under low pressure.

[0071] It should be noted that the type of epoxy resin is not limited in the present application. Exemplarily, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, and alicyclic epoxy resin.

[0072] In some embodiments of the present application, the curing agent is one or more of dicyandiamide, aromatic diamines, imidazoles, and hydrazides.

[0073] In some embodiments of the present application, the anisotropic conductive adhesive further comprises a diluent. Further, the anisotropic conductive adhesive comprises 1 to 50 parts of active diluent by mass. Exemplarily, the active diluent is 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, and values ​​between any two of the above values.

[0074] It should be noted that the diluent in this application is mainly used to adjust the viscosity of the conductive adhesive to make it easier to apply, coat or print. The type of diluent is not limited. Exemplarily, the active diluent is selected from one or more of propenyl glycidyl ether, phenyl glycidyl ether, diepoxy ethylene glycol diglycidyl ether, and resorcinol diglycidyl ether.

[0075] In some embodiments of the present application, the anisotropic conductive adhesive further comprises a thixotropic agent. Further, the anisotropic conductive adhesive comprises 0.5 to 15 parts of the thixotropic agent by mass. Exemplarily, the thixotropic agent is 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts, and values ​​between any two of the above values.

[0076] It is understood that the thixotropic agent can make the anisotropic conductive adhesive present a higher viscosity in a static state, and its viscosity will decrease when a shear force is applied (such as stirring or coating). This makes the anisotropic conductive adhesive more fluid during application, easy to coat or print, and can return to a higher viscosity after standing to avoid flowing.

[0077] It should be noted that the type of thixotropic agent is not limited in the present application. Exemplarily, the thixotropic agent is selected from one or more of fumed silica, precipitated silica, organic bentonite, asbestos, kaolin, attapulgite, and emulsion-processed vinyl chloride compounds.

[0078] The present invention also provides a method for preparing an anisotropic conductive adhesive, comprising the following steps:

[0079] S1 Preparation of core-shell structured conductive particles.

[0080] Exemplarily, a surfactant, liquid metal and deionized water are first added to a beaker, and ultrasonic treatment is performed for a certain period of time using an ultrasonic cleaning machine to obtain a liquid metal microsphere suspension. A reducing agent is then added to the liquid metal microsphere suspension, and ultrasonic treatment is performed for a certain period of time. The prepared ammonia solution is added to a silver salt solution to obtain a silver ammonia solution. Then, at a certain temperature, the liquid metal microspheres are added to the silver ammonia solution, stirred for reaction, and a dark brown LM@Ag conductive microsphere dispersion is obtained. Finally, washing and drying are performed to obtain LM@Ag composite conductive microsphere powder.

[0081] Optionally, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate, and polyvinyl pyrrolidone.

[0082] Optionally, the type of the liquid metal is one or more of gallium-indium liquid metal, gallium-indium-tin liquid metal, and indium-tin liquid metal.

[0083] Optionally, the reducing agent is one or more of glucose, potassium sodium tartrate, formaldehyde, and dimethylaminoborane.

[0084] Optionally, the silver salt is one or more of silver nitrate, silver chloride, silver bromide, and silver iodide halide.

[0085] Further, the mass ratio of the liquid metal to the silver salt is 1 to 5. Exemplarily, the mass ratio of the liquid metal to the silver salt is 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and values ​​between any two of the above values.

[0086] Further, the ultrasonic treatment time of the ultrasonic cleaning machine is 10 to 50 minutes. Exemplarily, the ultrasonic treatment time of the ultrasonic cleaning machine is 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, and a value between any two of the above values.

[0087] Furthermore, the chemical reaction temperature during the preparation of the composite conductive microspheres is 40-80° C. Exemplarily, the chemical reaction temperature is 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., and values ​​between any two of the above values.

[0088] Furthermore, the chemical reaction time during the preparation of the composite conductive microspheres is 5 to 60 minutes. Exemplarily, the chemical reaction time during the preparation of the composite conductive microspheres is 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes, and values ​​between any two of the above values.

[0089] S2: Mixing epoxy resin, curing agent and conductive particles according to a preset ratio to obtain anisotropic conductive adhesive.

[0090] Exemplarily, epoxy resin, curing agent and conductive particles are put into a mixing device according to a preset ratio, and are evenly mixed to obtain anisotropic conductive adhesive.

[0091] The embodiment of the present application further provides a polymer, which is formed by hot pressing and curing the above-mentioned anisotropic conductive adhesive or the anisotropic conductive adhesive obtained by the above-mentioned preparation method.

[0092] Further, the hot pressing curing temperature is 120-190° C. Exemplarily, the hot pressing curing temperature is 120° C., 125° C., 130° C., 135° C., 140° C., 145° C., 150° C., 155° C., 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C. and values ​​between any two of the above values.

[0093] Further, the heat pressing curing time is 4 to 15 seconds. Exemplarily, the heat pressing curing time is 4 seconds, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds, 15 seconds, and a value between any two of the above values.

[0094] The anisotropic conductive adhesive in the present application is further described below in conjunction with specific embodiments and experimental tests.

[0095] Example 1

[0096] (1) Preparation of core-shell conductive particles

[0097] First, add 0.5g polyvinyl pyrrolidone, 0.5g gallium indium liquid metal and 40mL deionized water into a beaker, and use an ultrasonic cleaner to ultrasonically treat for 20 minutes to obtain a liquid metal microsphere suspension. Then add 0.5g glucose to the liquid metal microsphere suspension and ultrasonicate for 10 minutes. Add ammonia solution to 5mL of silver nitrate solution (20mg / mL) to obtain a silver ammonia solution. Then, at 55°C, add the liquid metal microspheres to the silver ammonia solution, stir for 20min under heating conditions, and obtain a dark brown LM@Ag conductive microsphere dispersion. Finally, centrifuge, wash three times, and dry to obtain LM@Ag conductive microsphere powder.

[0098] The obtained metal microsphere suspension and LM@Ag conductive microsphere powder were tested by scanning electron microscope and particle size analyzer. The test results of the metal microsphere suspension are shown in Figure 1 As shown in Figure 2, the test results of LM@Ag conductive microsphere powder are as follows: Figure 2As shown, it can be seen that the average particle size of the prepared LM@Ag conductive microsphere powder is about 3 μm, and the particle distribution is relatively uniform. Figure 3 The cross-sectional scanning electron microscope image and element distribution map of LM@Ag conductive microspheres. Figure 3 It can be seen that the average thickness of the metal shell is about 90nm, and an intermediate phase is formed between the liquid metal and the metal shell.

[0099] (2) Preparation of anisotropic conductive adhesive and test samples

[0100] Calculated by mass, weigh the following: epoxy resin: 100 parts of bisphenol A epoxy resin; active diluent: 10 parts of ethylene glycol diglycidyl ether with diepoxy groups; curing agent: 20 parts of dicyandiamide; thixotropic agent: 5 parts of fumed silica; conductive particles: 30 parts of LM@Ag composite conductive microspheres. Figure 1 This is a scanning electron microscope image and particle size dispersion diagram of liquid metal ions, with an average particle size of about 3.2μm.

[0101] Prepare the raw materials according to the above ingredients and mass parts, mix them evenly to obtain anisotropic conductive adhesive. Fill the prepared anisotropic conductive adhesive into the dispensing needle tube. The prepared anisotropic conductive adhesive based on LM@Ag composite conductive microspheres is applied to the bonding RFID chip (R6 chip, size 465μm×400μm), and hot pressing curing is achieved by a hot pressing head. The hot pressing temperature is 190℃, the hot pressing time is 8s, and the hot pressing curing pressure is 1N. The schematic diagram of the hot pressing curing process is shown in the figure Figure 4 As shown, the SEM image of the cross-section of the anisotropic conductive adhesive bonded RFID chip is as follows Figure 5 shown.

[0102] Example 2

[0103] Compared with Example 1, the curing agent in Example 2 is 5 parts of imidazole adduct (PN23J) and 15 parts of dicyandiamide, and the other ingredients are controlled unchanged.

[0104] Example 3

[0105] Compared with Example 1, the curing agent in Example 3 is 10 parts of imidazole adduct (PN23J) and 10 parts of dicyandiamide, and other ingredients are controlled unchanged.

[0106] Example 4

[0107] Compared with Example 1, the curing agent in Example 4 is 15 parts of imidazole adduct (PN23J) and 5 parts of dicyandiamide, and the other ingredients are controlled unchanged.

[0108] Example 5

[0109] Compared with Example 1, the curing agent in Example 5 is 20 parts of imidazole adduct (PN23J), 0 parts of dicyandiamide, and other components are controlled unchanged.

[0110] Example 6

[0111] Compared with Example 3, the mass fraction of LM@Ag composite conductive microspheres in Example 6 is 20 parts, and other components remain unchanged.

[0112] Example 7

[0113] Compared with Example 3, the mass fraction of LM@Ag composite conductive microspheres in Example 7 is 10 parts, and other components are kept unchanged.

[0114] Example 8

[0115] Compared with Example 3, the mass fraction of LM@Ag composite conductive microspheres in Example 8 is 40 parts, and other components are kept unchanged.

[0116] Example 9

[0117] Compared with Example 3, the difference is that in the process of preparing the core-shell structured conductive particles in Example 9, the amount of silver nitrate solution used is 3.5 ml. The shell thickness of the prepared LM@Ag composite conductive microspheres is about 60 nm, and the other components are kept unchanged.

[0118] Example 10

[0119] Compared with Example 3, the amount of silver nitrate solution used in the process of preparing the core-shell structured conductive particles in Example 10 is 8 ml. The shell thickness of the prepared LM@Ag composite conductive microspheres is about 200 nm, and other components are kept unchanged.

[0120] Embodiment 11

[0121] Compared with Example 3, the amount of active epoxy diluent in Example 11 is 15 parts, and other components remain unchanged.

[0122] Example 12

[0123] Compared with Example 3, the amount of silver nitrate solution used in the process of preparing the core-shell structured conductive particles in Example 12 is 25 ml. The shell thickness of the prepared LM@Ag composite conductive microspheres is about 300 nm, and other components are kept unchanged.

[0124] Compared with Example 3, in Example 13, copper nitrate is used to replace silver nitrate in the process of preparing the conductive particles with a core-shell structure. The prepared conductive particles are LM@Cu composite conductive microspheres, the mass fraction of the conductive particles in the anisotropic glue is 30 parts, and the other components are kept unchanged.

[0125] Comparative Example 1

[0126] Compared with Example 3, the conductive particles in Comparative Example 1 (E) are liquid metal microspheres, the amount is 30 parts, and other components are controlled unchanged.

[0127] Comparative Example 2

[0128] Compared with Example 3, the conductive particles in Comparative Example 1 (E) are irregular Ni powders, the amount of which is 30 parts, and other components remain unchanged.

[0129] Comparative Example 3

[0130] Compared with Example 3, the conductive particles in Comparative Example 1 (E) are irregular Ni powders, the amount of which is 120 parts, and other components remain unchanged.

[0131] Performance Testing:

[0132] Adhesion strength: Use a welding strength tester to test the peeling force. Five samples of each sample need to be tested and the results are averaged.

[0133] Rheology: The viscosity was tested using a high-speed rotational rheometer with the test spacing set to 0.2 mm.

[0134] Curing reaction: DSC differential scanning calorimeter was used for testing. The heating rate was 10°C / min and the temperature scanning range was -50 to 250°C.

[0135] RFID tag cross-sectional observation: A cross-sectional view of an RFID tag encapsulated with an anisotropic conductive adhesive was observed using a scanning electron microscope.

[0136] RFID tag signal test: Use a tag comprehensive performance tester to test.

[0137] Reliability test: Use high temperature and high humidity accelerated aging test chamber and hot and cold shock cycle test chamber to test the samples. The test conditions of the high temperature and high speed accelerated aging test chamber are 85℃, RH 85%, hot and cold cycle conditions are -45~85℃, each cycle is 15min, and the samples are placed in the two test chambers for 7 days to test the changes in tag signals before and after aging.

[0138] Table 1

[0139]

[0140]

[0141] Depend on Figure 5 It can be seen that LM@Ag composite conductive microspheres are sandwiched between the chip electrode and the Al antenna to conduct the circuit. In the non-bonded area, LM@Ag composite conductive microspheres are dispersed in the resin matrix, and ACP (anisotropic conductive adhesive) plays a role of fixing and mechanical support.

[0142] Furthermore, a comprehensive performance tester for tags was used to test the working signal of the RFID tags encapsulated with the anisotropic conductive adhesive. It can be seen from Examples 1 to 13 and Table 1 that the anisotropic conductive adhesive based on the core-shell structure of the conductive particles and the composite conductive microspheres prepared in the present application can make the RFID tags work normally under a bonding pressure of 1N. The anisotropic conductive adhesives obtained in the examples of the present application are used to bond the RFID chip, and the minimum starting power of the RFID chip is less than 10dBm. The anisotropic conductive adhesive in the examples of the present application can better bond the chip to the RFID antenna.

[0143] It can be seen from Examples 1 to 5 that when the curing agent in the present application includes both imidazole adduct and dicyandiamide, the bonding strength is higher and it is beneficial to further reduce the minimum activation power of the RFID chip. Furthermore, when the ratio of imidazole adduct to dicyandiamide is close to 1:1, it is beneficial to further improve the bonding performance of the anisotropic conductive adhesive and further reduce the minimum activation power of the RFID chip, achieving unexpected results.

[0144] It can be seen from Examples 3 and 6 to 8 that when the conductive particles in the anisotropic conductive adhesive are about 30 parts by mass, it is beneficial to further reduce the minimum starting power of the RFID chip, and the anisotropic conductive adhesive still has a high bonding strength, achieving unexpected results.

[0145] It can be seen from Examples 3, 9 and 10 that when the shell thickness of the conductive particles is about 90 nm, it is beneficial to improve the bonding strength of the anisotropic conductive adhesive and to further reduce the minimum starting power of the RFID chip, achieving unexpected results.

[0146] It can be seen from Example 3, Example 13, Comparative Example 1 and Comparative Example 2 that, when the mass fraction of conductive particles in the anisotropic conductive adhesive is the same, the conductive particles with a core-shell structure added in the examples of the present application can significantly reduce the minimum startup power of the RFID chip. At the same time, it can be seen from Example 3 and Example 13 that, compared with the conductive particles having a shell layer of copper, the conductive particles having a shell layer of silver can further reduce the minimum startup power of the RFID chip, achieving an unexpected effect.

[0147] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An anisotropic conductive adhesive, comprising, by weight: 50 to 100 parts of epoxy resin; 0.5 to 30 parts of curing agent; as well as 10 to 40 parts of conductive particles with a core-shell structure, wherein the core layer of the conductive particles comprises liquid metal, and the shell layer of the conductive particles comprises a metal layer.

2. The anisotropic conductive adhesive according to claim 1, characterized in that: The thickness of the metal layer is 50nm to 500nm; and / or The particle size of the conductive particles is 1 μm to 5 μm; and / or The anisotropic conductive adhesive further comprises at least one of a diluent, a thixotropic agent, and an inorganic filler; and / or The conductive particles of the core-shell structure are 25 to 40 parts.

3. The anisotropic conductive adhesive according to claim 2, characterized in that: The liquid metal includes one or more of gallium, bismuth, cadmium, tin, lead, indium, bismuth-gallium alloy, gallium-indium alloy, gallium-indium-tin alloy, and indium-tin alloy; and / or The thickness of the metal layer is 60nm to 200nm; and / or The material of the metal layer includes at least one of silver, copper, aluminum, gold, nickel, and zinc; and / or The active diluent is 1 to 50 parts by mass; and / or The diluent comprises a reactive diluent, and the reactive diluent is selected from one or more of propenyl glycidyl ether, phenyl glycidyl ether, ethylene glycol bisglycidyl ether with diepoxy groups, and resorcinol bisglycidyl ether; and / or The thixotropic agent is 0.5 to 15 parts by mass; and / or The thixotropic agent is selected from one or more of fumed silica, precipitated silica, organic bentonite, asbestos, kaolin, attapulgite, and emulsion-processed vinyl chloride compounds.

4. The anisotropic conductive adhesive according to any one of claims 1 to 3, characterized in that: The liquid metal is a gallium-indium alloy, and the material of the metal layer is silver; and / or The thickness of the metal layer is 80nm-100nm.

5. The anisotropic conductive adhesive according to any one of claims 1 to 3, characterized in that: The epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, and alicyclic epoxy resin; and / or The curing agent is selected from one or more of dicyandiamide, aromatic diamines, imidazoles and hydrazides.

6. The anisotropic conductive adhesive according to claim 5, characterized in that: The curing agent consists of imidazoles and dicyandiamides, and the mass ratio of the imidazoles to the dicyandiamides is (5-15):(5-15).

7. The anisotropic conductive adhesive according to any one of claims 1 to 3, characterized in that: Under a bonding pressure of 1N to 3N, the anisotropic conductive adhesive is electrically conductive in the direction of the bonding pressure and electrically insulated in a direction perpendicular to the bonding pressure.

8. A method for preparing anisotropic conductive adhesive, the method comprising the following steps: Preparation of conductive particles with core-shell structure; Mixing epoxy resin, curing agent and the conductive particles of the core-shell structure according to a preset ratio to obtain anisotropic conductive adhesive; The core layer of the conductive particles includes liquid metal, the shell layer of the conductive particles includes a metal layer, and the thickness of the metal layer is 50 nm to 500 nm.

9. The preparation method according to claim 8, characterized in that: The step of preparing the conductive particles with a core-shell structure comprises: obtaining a liquid metal microsphere suspension and a silver ammonia solution; Adding the liquid metal microsphere suspension into the silver ammonia solution, stirring the reaction to obtain a dark brown conductive particle dispersion; Conductive particles with a core-shell structure are obtained by filtering and drying, wherein the core layer of the conductive particles comprises liquid metal, and the shell layer of the conductive particles comprises a silver layer.

10. An electronic component, characterized in that: The electronic component comprises a first electrical connection portion, a second electrical connection portion, and the anisotropic conductive adhesive according to any one of claims 1 to 7, wherein the anisotropic conductive adhesive is used to electrically connect the first electrical connection portion and the second electrical connection portion in a direction of bonding pressure.

Citation Information

Patent Citations

  • Preparation method of shell-core structure functional conductive particle

    CN110223798A

  • Anisotropic conductive adhesive and preparation method thereof

    CN110964469A